DIVERSIFICATION OF ENERGY DEPENDENCE IN UKRAINE - A. Stepanova (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The questions of energy diversification in Ukraine concerning sources and uses of energy are revealed. The influence of the energy dependence of the national security is discussed. The importance of diversification and international cooperation on equal terms with the field of energy supply is proved. The possible solutions of the energy dependence of Ukraine are defined with consideration of international experience and development of renewable energy and potential of our country.